A UV‐C LED‐based unit for continuous decontamination of the sheath fluid in a flow‐cytometric cell sorter. Issue 8 (8th July 2022) - Kirsch, Jenny; Heinrich, Kerstin; Kage, Daniel; Glaab, Johannes; Grothe, Benjamin; Volkmann, Konrad v.; Kaiser, Toralf
Abstract: Aseptic cell sorting is challenging, especially when a flow‐cytometric cell sorter is not operated in a sterile environment. The sheath fluid system of a cell sorter may be contaminated with germs such as bacteria, yeasts, viruses, or fungi. Thus, a regular chemical cleaning procedure is required to prepare a sorter for aseptic cell sorting by flushing the fluidic system. However, this procedure is time consuming, and most importantly, the researcher can never be sure that the cleaning process was successful. Here we present a method in which the sheath fluid of a cell sorter was decontaminated by irradiation with UV‐C light using a flow‐through principle. Using this principle, we were able to achieve a 5 log reduction of bacteria in the sheath fluid.